Change in the population reaction norm as the main cause of increased numbers and outbreaks of mass reproduction of insect pests (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The report presents a conceptual scheme of changing the reaction norm in a population of insect pests. When external conditions stabilize, this may be the main reason for the out breaks of such pests. Taking into account the above, a change in the definition of the r-strategist species is proposed.
Keywords: outbreaks, r-strategy species, population reaction norm, phenotypic diversity, exter nal conditions